2001
DOI: 10.1038/oby.2001.61
|View full text |Cite
|
Sign up to set email alerts
|

Neck Circumference as a Simple Screening Measure for Identifying Overweight and Obese Patients

Abstract: BEN-NOUN, LIUBOV (LOUBA), EZRA SOHAR, AND ARIE LAOR. Neck circumference as a simple screening measure for identifying overweight and obesity patients. Obes Res. 2001;9:470 -477. Objective: There are numerous methods of assessing overweight and obesity. We undertook an observational study to test a method of identifying overweight or obese patients solely by measuring the circumference of the neck. Research Methods and Procedures:A test sample and a second validation sample included 979 subjects (460 men and 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
291
1
34

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(346 citation statements)
references
References 21 publications
20
291
1
34
Order By: Relevance
“…Ben Noun et al, [9][10][11][12] observed relationship between changes in neck circumference and changes in blood pressure. They found that changes in systolic BP and diastolic BP correlated positively with changes in NC and other components of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ben Noun et al, [9][10][11][12] observed relationship between changes in neck circumference and changes in blood pressure. They found that changes in systolic BP and diastolic BP correlated positively with changes in NC and other components of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In a first cross sectional study by Ben-Noun et al, [9][10][11][12] which was done to identify overweight or obese patients solely by measuring the circumference of the neck, observed that NC >37cm for men and >34cm for women were the best cutoff levels for determining the subjects with BMI >25.0 kg/m 2 using the receiver output curve analysis. In our study we also observed same characteristics as NC 37 cm for men and 34 cm for women identified subjects with BMI >25.0 kg/m 2 with 75% to 86% sensitivity for men and 63% to 93% for women, 80% to 90% specificity for men and 80% to 100% for women.…”
Section: Discussionmentioning
confidence: 99%
“…Cruz and Goran 17 ). However, Ben-Noun et al 18 tested a method of identifying overweight or obese patients solely by measuring the circumference of the neck circumference (NC). Their results indicated a significant association between NC and body mass index (BMI), age, weight, waist circumference, hip circumference, and WHR.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] Moreover, there is some evidence demonstrating that NC is associated with cardiovascular risk factors, such as high waist and hip circumferences, elevated blood pressure values and high total cholesterol and glycemia levels. 12,13,17 However, even though optimal cutoff values for adults have been suggested and have been observed to be associated with cardiovascular risk factors (e.g. elevated blood pressure and insulin resistance), 20,21 there are no data in the literature regarding specific cutoffs for the elderly population.…”
Section: Introductionmentioning
confidence: 99%